Burden of diabetes in correctional facilities: A global systematic review and meta-analysis - Muhammed Shabil; Shilpa Gaidhane; Sorabh Lakhanpal; Sara Irshaidat; Suhas Ballal; Sanjay Kumar; Mahakshit Bhat; Shilpa Sharma; M. Ravi Kumar; Sarvesh Rustagi; Mahalaqua Nazli Khatib; Sunil Kumar Mishra; et al. (Journal of Clinical & Translational Endocrinology)
Background: Diabetes mellitus presents significant public health challenges worldwide. While its prevalence and management in the general population have been extensively studied, comprehensive research on diabetes among incarcerated individuals is lacking. This study aims to conduct a systematic review and meta-analysis to determine the prevalence of diabetes within the prison population. Methods: The systematic review included studies reporting on the prevalence of diabetes in prison populations. Searches were conducted in PubMed, Web of Science, and EMBASE from 2000 to November 4, 2023, with an update on December 15, 2023. Nested Knowledge web software was utilized for screening and data extraction. Quality assessment was conducted using the JBI tool. A meta-analysis was performed using a random-effects model in R software version 4.3. Results: Thirty-three studies were included, encompassing 807,617 participants, with 67,291 reported as patients with diabetes. The pooled prevalence of diabetes in prison populations was found to be 7.1% (95% CI: 4.9% to 10.1%), exhibiting high heterogeneity (I2 = 100%). Subgroup analysis revealed significant geographical variability: the United States had a prevalence of 9% (95% CI: 4 %to 17 %), Italy 5% (95% CI: 0% to 40 %), Iran 10% (95% CI: 7 % to 15 %), and Egypt 21% (95% CI: 14% to 28 %). Notable variations in prevalence were also observed in countries like France, Australia, Taiwan, India, the UK, Spain, Brazil, and Sub-Saharan Africa. An LFK index of −3.3 indicated the presence of publication bias. Conclusion: The study reveals that diabetes mellitus is a significant health concern in prisons, with a prevalence of 7.1%, comparable to that in the general population. The marked variability across studies indicates the challenges of diabetes management in correctional settings. These findings highlight the need for tailored healthcare strategies, considering prisons’ unique challenges and risk factors.